Automated Irrigation System through Wireless Moisture Sensor Network - Md Shukor Bin Abd Rahim, Md Shukor (2009)
This project is meant to efficiently improve the water usage in a farm’s irrigation system. The objective of this project is to develop a wireless moisture sensor network system that can monitor and automate the irrigation system. The monitoring operation will collect data and the automatic operation is to automate the irrigation system using the data collected during the monitoring process.